Modelagem da extinção interestelar na direção de supernovas do tipo Ia - Torres, Tereza Cristina Santos (2018)
The accuracy and precision of cosmological results obtained from studies of Type Ia supernovae (SNe Ia) strongly depend on the control of systematic uncertainties. The modeling of both Galactic and the host galaxy extinction is a critical step in characterizing supernovae effects, thus its improvement can provide a significantly better way of their usage. Using the Cardelli, Clayton & Mathis (CCM) extinction law we have elaborated a method for reproducing the observed SN spectra by adjusting five parameters, namely Av and Rv for both Milky Way and SN host galaxy, also the SN redshift. In this manner, the fine tuning for both Galactic and the host galaxy extinction is achieved. We have used two different SNe Ia templates and the Harvard-Smithsonian Center for Astrophysics (CfA) supernova catalogue with more than 2600 SNe Ia observed spectra. The comparisons of the modeled spectra with the observed ones are presented, and the obtained parameters are thoroughly discussed. We have estimated parameters for 80 SNe Ia, covering 1080 spectra with epochs ranging from -20 to 50 days.